Pollen Provisioning Enhances the Performance of Amblydromalus limonicus on an Unsuitable Prey - Samaras, Konstantinos; Pappas, Maria L.; Fytas, Evangelos; Broufas, George D. (Frontiers in Ecology and Evolution, 2019)
Amblydromalus limonicus is a polyphagous phytoseiid predator used for the biological control of thrips and whiteflies in greenhouse crops. Besides various prey species, A. limonicus can also feed on pollen of different plants. Cattail pollen has been previously shown to be suitable for the development and reproduction of A. limonicus. Hence, it could sustain its populations in periods of prey scarcity. In the present study, we hypothesized that pollen provisioning may benefit A. limonicus in mixed diets with prey of low quality, such as spider mites and thus, positively impact ecosystem services provided by this predator. For this, the performance and predation efficiency of A. limonicus against spider mites was assessed in the presence or absence of pollen. Our results show that pollen significantly shortens the developmental time and increases the survival and oviposition of the predator when mixed with spider mites, although it negatively affects its predation rate. Nevertheless, pollen enhances the maintenance of juvenile predators on the leaf by substantially decreasing their dispersal rate in the mixed diet with spider mites. In addition, the intrinsic rate of population increase (rm) of A. limonicus feeding with spider mites increased with the addition of pollen suggesting an increase in its population. Cattail pollen as supplementary food may thus expand the prey species range that A. limonicus could exploit. It can also enhance ecosystem services provided against other pests (thrips and whiteflies) by positively affecting the increase of A. limonicus population.